Case Report: Co-occurrence of tubulitis and SARS-CoV-2 specific T-cells in a kidney transplant recipient - Stervbo, Ulrik; Seidel, Maximilian; Uszkoreit, Julian; Kaliszczyk, Sviatlana; Anft, Moritz; Eisenacher, Martin; Westhoff, Timm H.; Babel, Nina (Frontiers in Transplantation, 2025)
BackgroundKidney transplantation is associated with an increased risk of severe COVID-19 disease. Additionally, cells of the kidney express ACE-2 making them a potential target of the SARS-CoV-2 virus. Both uncontrolled viral replication and T-cell receptor (TCR) mediated cellular immunity towards the infected cells could lead to tissue destruction in the kidney. In cases where pathological findings are not always capable of providing definitive diagnosis, insights into the TCR repertoire could offer valuable information. Here we present a case of potentially infection driven tubulitis in a kidney transplant patient.MethodsThe source of kidney infiltrating T-cells was assessed through next generation TCR sequencing. Using cells from the living donor and overlapping peptide pool of SARS-CoV-2 S-, N-, and M-protein (Wuhan variant), antigen specific T-cells were isolated from peripheral blood by overnight stimulation and subsequent isolation using antibodies and magnetic beads against CD154 and CD137. The clonotypes of these two samples were compared to the clonotypes in a single kidney biopsy cylinder.ResultsWe found that 11.1% of the repertoire of the kidney infiltrating T cells were identical to SARS-CoV-2 specific T-cells in the periphery, and only 3.1% of the repertoire was identical to allo-specific TCRs. We also observed substantial overlap between the TCR repertoires of virus-specific and donor-specific T cells, with high similarity and even identical TCR sequences present in both populations. The TCRs with dual specificity constituted a larger proportion of the allo-specific than the virus specific population. These results indicate that SARS-CoV-2 specific T-cells may directly spill into an allo-specific T cell response and that either class of T-cells may cause the observed tubulitis.ConclusionTCR-seq of whole biopsies is a method to evaluate the ingragraft TCR repertoire can complement routine pathology and provide further insights into the mechanisms underlying a diagnosis.